ANALISIS KEBIJAKAN PENGELOLAAN PAJAK DAERAH DALAM MENINGKATKAN PAD DI KABUPATEN BANDUNG - Riswati Riswati (Fakultas Manajemen Pemerintahan, Institut Pemerintahan Dalam Negeri, 2022)
AbstractThe purpose of this research is to find out how far the increase in local revenue through local tax management mechanisms. Regional Revenue Agency is the Agency responsible for managing local revenue in Bandung Regency. For this reason, researchers are interested in conducting research related to